Nurses' experiences of psychosocial care needs of children with thalassaemia and their families in Jordan: A phenomenological study - Ghada Mohammad Abu Shosha; Mahmoud Al‐Kalaldeh; Noordeen Shoqirat (Wiley, 2022)
Abstract Aim To explore the experiences of Jordanian nurses regarding the psychosocial care needs of children with thalassaemia and their families. Design A descriptive phenomenological approach was employed. Methods A purposive sampling strategy was used to select 10 nurses who had experience in caring for children with thalassaemia. Unstructured, face‐to‐face interviews were conducted. Coliazzi's data analysis process was applied. Results The analysis revealed three major themes: (1) valuing psychosocial support; (2) caring for paediatric patients needs certain competencies in nurses and (3) barriers to providing psychosocial care. Nurses expressed the importance of providing psychosocial care. A lack of specialists in psychosocial care as well as a lack of screening tools, and entertainment facilities for children was identified to be impeding effective psychosocial care. Implementing training programmes for nurses concerning providing psychosocial care and making the appropriate changes in nursing curricula at the educational level are recommended.